The effect of the team games tournament learning model assisted by question card media on student learning outcomes - Najihan Arizka; Khairuna Khairuna (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2022)
This study aimed to improve student learning outcomes and determine the effect of the Team Games Tournament (TGT) learning model assisted by question card media on human reproductive system material. This study employed a quantitative research type, with a quasi-experimental research design. Class XI science 1 student totalled 36, and class XI science 2 students totalled 36, with research instruments consisting of hand-held elective tests administered during post-test and pre-test. Using version 20 of the SPSS software, descriptive and paired simple t-test analyses of data were conducted. The average pre-test scores for the experimental group were 24.17, whereas those for the control group were 22,78. The average post-test scores of the experimental group were 80,14, on the other hand, those of the control group were 69. In the paired simple t-test, the 2-tailed sign value was 0,00 < 0,05, and the tcount > ttable which was 47,61 > 2,03. This demonstrates that the TGT learning model assisted by media question cards can enhance learning outcomes and significantly impact the biology learning process. TGT learning aided by question cards may be one way for educators to optimise learning processes and outcomes. Abstrak Penelitian ini bertujuan untuk mengetahui pengaruh model pembelajaran Team Games Tournament (TGT) berbantuan media question card pada materi sistem reproduksi manusia dan meningkatkan hasil belajar peserta didik SMA kelas XI IPA. Jenis penelitian berupa penelitian kuantitatif dengan desain penelitian berupa  quasi eksperimen. Sampel penelitian yaitu siswa kelas XI IPA 1 berjumlah 36 siswa dan kelas XI IPA 2 berjumlah 36 siswa dengan instrument penelitian berupa tes pilihan bergandan yang diberikan saat dilakukan uji post-test dan pre-test. Analisis data berupa analisis deskriptif dan uji paired simple t-test dengan bantuan software SPSS versi 20. Adapun hasil rata-rata pre-test pada kelas eksperimen yaitu 24,17 dan pada kelas kontrol yaitu 22,78. Hasil rata-rata post-test kelas eksperimen yaitu 80,14 dan  kelas kontrol yaitu 69,72.  Pada uji paired simple t-test nilai sig. 2-tailed 0,00 < 0,05 dengan nilai thitung > ttabel yaitu 47,61 > 2,03. Hal ini menunjukan bahwa model pembelajaran TGT berbantuan media question card dapat meningkatkan hasil belajar siswa dan juga memiliki pengaruh yang signifikan dalam proses pembelajaran biologi. Pembelajaran TGT berbantuan question card dapat menjadi salah satu solusi bagi guru untuk mengoptimalkan proses dan hasil belajar.